KAJIAN IDENTIFIKASI JUDGMENTAL BIASES DALAM ESTIMASI DURASI PENGERJAAN PROYEK BERBASIS SERIOUS GAMING - , TULUS SILAS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Project is a systematic activity that has unique and temporary character. Project has risk potency, so that it is necessary to have an identification process and analysis of project risk. One of many risks that emerges in a project is lack of historical data. This implicates to the necessity of subjective judgment from the project executor, such as while estimating project duration time. However, subjective judgment could implicate bias. Bias could emerge as a result of heuristic, a shortcut to help people in decision making. Serious gaming is a type of game that aims to an influence in learning purpose and expects a serious player. This research would identify bias in estimating project duration time which analogized by serious simulation gaming. This research method is experimental study. There are 90 students as respondents, which grouped into 30 groups. Respondents are categorized as novice since they never play the game before. The game is Moonbase Alpha, which developed by NASA. There are two factors considered in this research, which are estimator subject and type of coordination in game. These two factors generate 2 2 design of experiment with four times of experiment. As a result, there are four groups of treatment and each group will play four times. There is one stage of experiment which is a competitive stage to observe the effect of reward in the successful rate of project. Before starting the game, respondents have to estimate an initial value which is defined as estimating value of project duration. This value will be compared with actual value of playing the game and will be defined as accuracy. There are eight results of this research. Learning curve phenomenon is not found in this observation, which only takes four times of experiment. Moreover, observation does not find any effect of anchoring stimulus in estimating duration. Anchoring is known as one of bias variety. Observation discovers that a bias comes up to whole respondent with negative bias. It means it has an aggressive estimation with -1.38681 as a value. Experiment does not discover an interaction between treatments and there is bias on individual estimation and group estimation. Experiment does not also discover any significant difference between coordination and successful of project, which rated from the diminution of actual time. Reward concepts does not influence the player since there is no significant difference of actual time on competitive stage and uncompetitive stage. Data distribution pattern follow Loglogistic Distribution which 8.95 as location value